2023
DOI: 10.31219/osf.io/vd5qt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of the source of prebunks and debunks of misinformation: Online experiments in four EU countries

Abstract: Misinformation surrounding crises poses a significant challenge for public institutions. Understanding the relative effectiveness of different types of interventions to counter misinformation and understanding which segments of the population are most or least receptive to them, is crucial. We conduct a preregistered online experiment involving 5,228 participants from Germany, Greece, Ireland, and Poland. Participants were exposed to misinformation on climate change or Covid-19. In addition, they were pre-empt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In this field report, we have shown how health-related misinformation is a growing challenge for the medical programmes that MSF operates, and for the humanitarian sector at large (Bruns et al, 2022). It can erode trust in healthcare interventions and negatively affect people's health-seeking behaviour, thereby resulting in poor health outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…In this field report, we have shown how health-related misinformation is a growing challenge for the medical programmes that MSF operates, and for the humanitarian sector at large (Bruns et al, 2022). It can erode trust in healthcare interventions and negatively affect people's health-seeking behaviour, thereby resulting in poor health outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Inoculation interventions have also been found to be perceived as more manipulative than debunking interventions presented after misinformation or persuasion attempts (Bruns et al, 2023). Considering the polarized and politicized debate on vaccination, and the existence of vaccine mandates, it is possible that vaccination is perceived as a freedom-threatening topic.…”
Section: Discussionmentioning
confidence: 99%
“…However, a follow-up study failed to replicate a backfire effect (Haglin, 2017), and the generalizability of the findings of two studies that report a backfire effect (Pluviano et al, 2017, 2019) is limited due to very small sample sizes (N = 120; N = 60). In fact, large-sample studies (N ≈ 13.000) across several countries (N = 13) revealed that corrections of vaccination misinformation are effective during a pandemic and that there is little evidence of backfire (Bruns et al, 2023; Porter et al, 2023).…”
Section: Responding To Vaccination Misinformationmentioning
confidence: 99%
“…Several studies compare inoculation interventions against impactful vaccination misinformation, revealing protective effects against the impact of misinformation (Bruns et al, 2023; Piltch-Loeb et al, 2022; Vivion et al, 2022; Wong, 2016). Among these studies are large-enough sample studies (N > 1000) that find the benefits of inoculation to be robust across countries (Bruns et al, 2023) and across variations of different types of inoculation interventions (Piltch-Loeb et al, 2022).…”
Section: Preventing the Impact Of Vaccination Misinformationmentioning
confidence: 99%
See 1 more Smart Citation